2020
DOI: 10.30534/ijatcse/2020/85952020
|View full text |Cite
|
Sign up to set email alerts
|

Cloud ERP in Malaysia: Benefits, Challenges, and Opportunities

Abstract: Cloud ERP systems are the recent trend of ERP systems and Cloud ERP is experiencing tremendous growth as well as it is considered as an alternative to local ERP systems due to its benefits associated with the deployment of cloud ERP compared to traditional ERP and the other characteristics that cloud computing technology bring it, cloud ERP does not require much prior investment and can be deployed immediately. Cloud ERP systems provide several advantages for small and medium businesses (SMEs). However, the ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 34 publications
(46 reference statements)
0
2
0
1
Order By: Relevance
“…Jurnal Teknik Informatika dan Sistem Informasi e-ISSN : Volume 9 Nomor 3 Desember 2023 I. PENDAHULUAN Enterprise Resource Planning (ERP) adalah salah satu sistem informasi yang paling penting dan paling populer untuk perusahaan bisnis, ERP pertama kali digunakan pada tahun 1990. Ini disebut sebagai sistem informasi terintegrasi yang digunakan untuk mengintegrasikan setiap fungsi departemen melalui seluruh organisasi dan untuk menyediakan komunikasi antara mereka dan pemasok [1]. Sistem perencanaan sumber daya perusahaan ERP menjamin pelanggan mereka beberapa keuntungan dengan sistem ERP mereka.…”
Section: P-issn : 2443-2210unclassified
“…Jurnal Teknik Informatika dan Sistem Informasi e-ISSN : Volume 9 Nomor 3 Desember 2023 I. PENDAHULUAN Enterprise Resource Planning (ERP) adalah salah satu sistem informasi yang paling penting dan paling populer untuk perusahaan bisnis, ERP pertama kali digunakan pada tahun 1990. Ini disebut sebagai sistem informasi terintegrasi yang digunakan untuk mengintegrasikan setiap fungsi departemen melalui seluruh organisasi dan untuk menyediakan komunikasi antara mereka dan pemasok [1]. Sistem perencanaan sumber daya perusahaan ERP menjamin pelanggan mereka beberapa keuntungan dengan sistem ERP mereka.…”
Section: P-issn : 2443-2210unclassified
“…In a Swedish study, the users of cloud ERP benefited in being able to enhance their business to go mobile, run their business more globally, decrease large up-front investment costs, save on-going technology costs and remove the need for maintenance, and management of the cloud ERP [99]. Further, Razzaq and Mohammed [100] found that the adoption of cloud ERP systems in Malaysian SMEs can have several benefits, such as low implementation costs, reduced staff to support and maintain the system, and reduced implementation time of IT projects. Isma'ili et al [101] deployed the diffusion of innovations (DOI) and TOE frameworks to examine the adoption of cloud ERP systems in Australian SMEs and their study revealed that organizational factors (top management support, firm size, IS knowledge and innovativeness of the organization), technological factors (relative advantage to current system, trialability to test performance of the system, cost saving and compatibility), and environmental factors (external computing support and market scope) were found to have a positive impact.…”
Section: Adoption Of Cloud Erp In Smesmentioning
confidence: 99%
“…The model showed a satisfactory fit of collected data on the CFI, TLI, and IFI indices with values more than the cutoff value of > 0.9 (0.973, 0.973, and 0.976, respectively) [86], [87]. In addition, the rootmean-square error of approximation (RMSEA) was 0.020, and that was lower than the suggested threshold of < 0.10 [88], [90]. Furthermore, the fact that the comparative CMIN/χ2, χ2/df, (1.224) has been less than 5 revealed the good fit of the model [89], [90].…”
Section: Goodness Of Fit Indicesmentioning
confidence: 99%